2020
DOI: 10.7759/cureus.10184
|View full text |Cite
|
Sign up to set email alerts
|

Synovitis, Acne, Pustulosis, Hyperostosis, Osteitis (SAPHO): An Interesting Clinical Syndrome

Abstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome is a rare disorder that classically involves the musculoskeletal system, i.e. bone, joint and skin. The exact pathogenesis of this syndrome is unknown. However, autoimmunity, infections, immune malfunction and genetic factors are attributed to its pathophysiology. Bone and joint involvements are the hallmark of SAPHO syndrome and not necessarily require cutaneous involvement at the time of diagnosis. X-ray of the affected joints could sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The difficulty in recognizing it is due to the wide diversity of signs and symptoms 3,4 . Bone scintigraphy is an important examination method, but only a small number of patients have the typical “bull’s head” sign, which brings challenges to the diagnosis 5–8 . 68 Ga-DOTA-FAPI-04 is a novel PET agent that has been shown to be promising for imaging tumors 9,10 .…”
mentioning
confidence: 99%
“…The difficulty in recognizing it is due to the wide diversity of signs and symptoms 3,4 . Bone scintigraphy is an important examination method, but only a small number of patients have the typical “bull’s head” sign, which brings challenges to the diagnosis 5–8 . 68 Ga-DOTA-FAPI-04 is a novel PET agent that has been shown to be promising for imaging tumors 9,10 .…”
mentioning
confidence: 99%
“…However, it is believed to be related to genetic factors, infections, and immune dysregulation. 157 As in Schnitzler's syndrome and AOSD, overproduction of IL-1β was also reported in SAPHO syndrome. 158 Studies have shown dysregulation of cytokines, including IL-1β, IL-8, IL-17, IL-18, and TNF-α, to be potentially involved in the pathogenesis of SAPHO.…”
Section: Pathogenesismentioning
confidence: 93%
“…Conventional treatments for SAPHO include NSAIDs, DMARDs, glucocorticoids or corticosteroids, bisphosphonates and antibiotics. 157 , 167 , 179 NSAIDs, DMARDs, glucocorticoids or corticosteroid, bisphosphonates and antibiotics have also been used as conventional treatments for CRMO/CNO. 180 182 Pamidronate, a bisphosphonate, has shown efficacy on osteoarticular manifestations of SAPHO, but did not improve cutaneous lesions.…”
Section: Sapho/crmso/cnomentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Due to the lack of treatment data as well as the variations in clinical manifestations, there is no treatment modality that has been determined to be the best for patients suffering from SAPHO syndrome. 11,12 We report a case of the disease with typical clinical findings. We report this case, citing the rarity of this uncommon entity.…”
mentioning
confidence: 96%